Ethics in research and combating academic plagiarism: an educational practice using the inverted classroom - Silva, Leonardo Henrique (2020)
The present work has as object an educational practice, in the format of a short course, aimed at clarifying ethics in research and combating academic plagiarism, carried out using the active methodology inverted classroom. The objective was to report the planning, execution and evaluation of this educational practice. The theoretical framework was based on authors such as Krokoscz (2012), Valente (2014), among others, in addition to guidance from Capes and Brazilian legislation. With a descriptive character of a qualitative approach, the experience was based on a bibliographic review, in order to reference the theme worked, in addition to the application of a questionnaire to collect data from the diagnostic evaluation. For the purpose of results, the study pointed out that the inverted classroom contributes substantially to the formation of more critical students, who express their own opinions, instigate their autonomy and enrich the interaction with the teacher and between the students themselves. At the end of the educational practice, it was found that the mini-course was an efficient tool to help in the research training process of the participating students.